Our future climate (World Meteorological Organization GenevaCH, 2003)
Looks at projections for the future state of the climate and concludes that there should be greater emphasis on assessing regional impacts of climate change and appropriate mitigation and adaptation strategies need to given.
Keywords: CLIMATE